Seismic vulnerability assessment of non-seismically designed buildings in moderate earthquake zone - Noor Sheena Herayani Harith; Shahrum Abdullah; Nur Izzati Husna Hassan; Samnursidah Samir; Mohd Irwan Adiyanto; Reni Suryanita; Sheikh Mohd Iqbal S. Zainal Abidin (Horizon Research Publishing, 2025)
This study evaluates the seismic vulnerability of non-seismically designed buildings in moderate earthquake located in Sabah, Borneo, East Malaysia using the FEMA P-154 Rapid Visual Screening (RVS) methodology and EMS-98 damage descriptions. The buildings, primarily constructed between the 1970s and early 2000s, were designed to support gravity and wind loads rather than seismic forces. Although it is on the tectonically stable southern Eurasia plate, the region experienced significant building damage during a magnitude Mw 6 earthquake in 2015 due to local faults. Field assessments of 215 buildings collected data on characteristics such as number of stories, construction year, occupancy, soil type, geological hazards, pounding, structural irregularities, and exterior falling hazards. Damage levels were categorized by structural type, including concrete moment-resisting frames (C1), concrete frames with unreinforced masonry infills (C3), and light wood frames (W1). The results indicate that in Ranau, 4%, 20%, 9%, and 68% of buildings were categorized as Levels 1, 2, 3, and 4 damage categories, respectively. In Lahad Datu, 62% and 38% were classified as Levels 3 and 4. Vertical irregularities, such as short columns in Ranau and split-level configurations in Lahad Datu, along with horizontal irregularities such as reentrant corners and misaligned beam-column connections, contributed significantly to structural vulnerability. These findings highlight the critical influence of architectural design on the reduction of seismic risk in moderate seismic regions and the need to improve design strategies for earthquake resilience.